How I Speak Defines What I Do: Effects of the Functional Language Proficiency of Host Country Employees on Their Unethical Pro-organizational Behavior - Shen, Ya Xi; Zhang, Chuang; Zuo, Lamei; Zhou, Xingxing; Deng, Xuhui; Zhang, Long (Frontiers in Psychology, 2022)
Functional language has been used in many multinational corporations (MNCs) as a way to overcome the problems caused by the coexistence of multiple languages in the workplace. The existing literature has explored the importance, adoption, and effectiveness of functional language. Yet, how functional language shapes host country employees’ moral cognition and behavior is insufficiently researched. Guided by the Social Identity Theory, this paper shows that host country employees’ functional language proficiency (i.e., English) enhances their unethical pro-organizational behavior through their linguistic group identification and moral disengagement. We tested our predictions using the data collected from 309 full-time host country employees through an online survey, and the results generally supported our hypotheses. The findings make contributions to both international management and language literature and organizational moral behavior literature.